The Contractual Position of Directors in Commercial Companies in Slovene Law - Darja Senčur Peček (Zbornik Radova Pravnog Fakulteta u Splitu, 2008)
In the Republic of Slovenia, the Companies Act in force regulates the position of directors only from the perspective of the functioning of a commercial company and not also from the perspective of the protection of their personal position. With reference to such, the Companies Act suggests that a contract be concluded between the commercial company and its director (a contract to perform the function of director). In practice, the aforementioned contract is as a general rule concluded as an employment contract and only rarely as a civil-law contact. The Employment Relations Act namely allows that a contractual relation between a company and a director be regulated as an employment relation and at the same time determines certain particularities of the labour-law position of directors, which the author discusses in the present article. The question that the author raises in this respect is whether and under what conditions a contract to perform the function of director can be an employment contract. Employment contracts namely regulate employment relations which are defi ned by the subordinate position of employees and the condition of work carried out upon instructions provided by employers and under their supervision.